Transforming Project Management with Artificial Intelligence: Bibliometric Analysis and Systematic Literature Review - Muhammad, Fathan; Raharjo, Teguh; Trisnawaty, Ni Wayan (SAFE-Network, 2026)
Despite the growing importance of project management to ensure organization success, the rate of project failures remains high, which indicates the need to apply modern methods. Latest innovations in Artificial Intelligence (AI) have been used to address challenges in the field. This study aims to conduct Bibliometric Analysis and Systematic Literature Review (SLR) to investigate the implementation of AI in project management, challenges faced, and the impact of the results. The study identifies four major trends where AI is applied within project management: prediction and monitoring, work automation, interaction and collaboration through immersive technologies, and knowledge management enhancement. The study encountered several challenges, including high implementation costs, a lack of senior management commitment, cultural resistance, limited access to real-time data, strategy misalignment, and data privacy concerns, all of which posed barriers to the study. On the other hand, the results show that the use of AI has various impacts, including increased productivity, better decision-making, and higher project success rates. This study covers AI in project management over the past recent five years as a novelty, offers a comprehensive classification of application, challenges and impacts, and fills the research gap left by the previous study. By bringing these insights together, this study contributes to deeper understanding of how AI is transforming project management and provides guidance for future implementations.